Creativity and Innovation: Current Practices through Teaching Methods in Secondary Schools - Wedikandage, L.N.P. (International Journal of Research and Innovation in Social Science, 2024)
Creativity involves creating something new, such as a new problem solution, method, or artistic object or form. Creativity in the curriculum is a student-centred, thematic approach to teaching that supports natural curiosity and stimulates creativity, enhancing learning through imaginative methods. Effective teaching necessitates flexibility, creativity, and responsibility to create an educational environment that caters to the individual needs of the learner. Despite the implementation of various teaching and learning approaches, 21st-century education still faces numerous challenges in Sri Lanka. However, the younger generations and teachers are advancing by incorporating creativity and innovation into their teaching and learning activities. The major goal of this study was to identify the current practices of creativity and innovation through teaching methods in secondary schools. The mixed method was used as a research method. The sample was comprised of 10 teachers and 115 students in secondary schools in Colombo District. Data were collected through questionnaires and interviews. Qualitative material was thematically analysed by hand and quantitatively through SPSS. The research found that most of the teachers used interactive lessons, problem-solving methods, peer teaching, project-based learning, blended learning, and peer feedback for the development of their creativity in the classroom. Furthermore, creativity can be fostered through direct instruction in a supportive classroom environment, focusing on powerful questions and problems rather than group work with a teacher as a facilitator. This study suggests that teachers should make an effort to educate students using student-centred learning rather than traditional teaching methods in order to ensure that students’ creativity and innovation skills improve.
Keywords: Creativity; innovations; methods; practices; secondary schools